The Innovation of Pesantren Development in Aceh Province through the Effectiveness of Organizational Culture - Siregar, Fauzan Ahmad; Prasetyo, Muhammad Anggung Manumanoso (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aimed to reveal the Dayah Perbatasan innovation based on the concept of organization development. Dayah Perbatasan is a government-affiliated Islamic boarding school educational institution. Operatively, Dayah Perbatasan is under Aceh province’s education department. The research method used in descriptive qualitative approach. The subject of this study were pesantren leaders, school principal, vice of curriculum and pesantren senior teacher. The data collection technique used observation, interviews, focus group interviews and analysis of documentation materials. The data were analyzed by using the constant comparative analysis method. Based on the result, there were three innovations in the Dayah Perbatasan, first work engagement; second, leadership trust and the last organization management; These three innovations could lead the Dayah Perbatasan to be an innovative Islamic Boarding School in Aceh Province. This study has the originality of the concept value of developing pesantren government-style. In addition, the study adopted the development theory of change management organizations integrated with various factors related to boarding school changes.